Failures in software project management – are we alone? A comparison with construction industry (The Journal of Modern Project Management, 2022)
Unfortunately software development projects have long been identified with budget complications, delays and failure concerning scope. The widely quoted CHAOS Reports of the Standish Group, whose first results were released in 1994, find that while this situation has improved, deviations from the plan continue to be present in a majority of projects. In this paper we study the current state of success in software development projects, contrasting their results with those of civil engineering projects. The obtained results showed the relative success that has been achieved in the industries studied in terms of meeting deadlines, budgets and scope. Although differences do exist, several similarities were found.